2020
DOI: 10.1097/scs.0000000000006099
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Gonial Angle on the Initial Biomechanical Stability of the Plate Osteosynthesis in Polyurethane Mandibles With Angle Fractures

Abstract: The aim of the present study was to examine the biomechanical stability of the mandibular angle fractures (MAF) fixated with standard titanium miniplates in polyurethane models with different gonial angles (GA). Three custom molds were prepared for 3-dimensional printed mandibles with low, normal and high GA. Twenty polyurethane replicas were cast per group and standard MAFs were created on each sample. Fractures were stabilized with 1 4-hole standard titanium miniplate inserted over the superior alveolar bord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…LGA, NGA, and HGA correspond to horizontal, normal, and vertical growth patterns, respectively. According to CT and ultrasound, the cross-section of the masticatory muscles in HGA individuals (vertical growth pattern) was smaller than that in NGA and LGA individuals [ 17 , 37 , 38 , 39 ]. Moreover, the muscle morphology in HGA individuals results in relatively lower masticatory force or function, which leads to a reduction in cortical bone thickness at the angle of mandible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LGA, NGA, and HGA correspond to horizontal, normal, and vertical growth patterns, respectively. According to CT and ultrasound, the cross-section of the masticatory muscles in HGA individuals (vertical growth pattern) was smaller than that in NGA and LGA individuals [ 17 , 37 , 38 , 39 ]. Moreover, the muscle morphology in HGA individuals results in relatively lower masticatory force or function, which leads to a reduction in cortical bone thickness at the angle of mandible.…”
Section: Discussionmentioning
confidence: 99%
“…The gonial angle (GA) is an anthropometric parameter used for assessment of the mandibular growth pattern [ 8 ]. Low gonial angle (LGA), normal gonial angle (NGA), and high gonial angle (HGA) correspond to horizontal, normal, and vertical growth, respectively [ 17 ]. Also, evidence shows that a vertical growth pattern is correlated with a shorter ramus height [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sirin et al . [ 21 ] studied the biomechanical stability of mandibular angle fractures with different gonial angles. Their study on polyurethane mandibles revealed higher displacement in the high gonial angle group as compared to both normal and low-angle groups, both at molar and incisal loading.…”
Section: Discussionmentioning
confidence: 99%
“…Two acrylic templates for the bilateral fracture lines and four for plate insertion were prepared. A box cutter was positioned over the fracture line and a rubber headed mallet was used to drive the box cutter into the fracture line until complete separation occurred [14]. The fracture segments were checked and then repositioned using the plate template.…”
Section: Fracture Linesmentioning
confidence: 99%